If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -2)(-6x + 4) = 0 Reorder the terms: (-2 + 3x)(-6x + 4) = 0 Reorder the terms: (-2 + 3x)(4 + -6x) = 0 Multiply (-2 + 3x) * (4 + -6x) (-2(4 + -6x) + 3x * (4 + -6x)) = 0 ((4 * -2 + -6x * -2) + 3x * (4 + -6x)) = 0 ((-8 + 12x) + 3x * (4 + -6x)) = 0 (-8 + 12x + (4 * 3x + -6x * 3x)) = 0 (-8 + 12x + (12x + -18x2)) = 0 Combine like terms: 12x + 12x = 24x (-8 + 24x + -18x2) = 0 Solving -8 + 24x + -18x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2'. 2(-4 + 12x + -9x2) = 0 Factor a trinomial. 2((-2 + 3x)(2 + -3x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-2 + 3x)' equal to zero and attempt to solve: Simplifying -2 + 3x = 0 Solving -2 + 3x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 3x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 3x = 0 + 2 3x = 0 + 2 Combine like terms: 0 + 2 = 2 3x = 2 Divide each side by '3'. x = 0.6666666667 Simplifying x = 0.6666666667Subproblem 2
Set the factor '(2 + -3x)' equal to zero and attempt to solve: Simplifying 2 + -3x = 0 Solving 2 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -3x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -3x = 0 + -2 -3x = 0 + -2 Combine like terms: 0 + -2 = -2 -3x = -2 Divide each side by '-3'. x = 0.6666666667 Simplifying x = 0.6666666667Solution
x = {0.6666666667, 0.6666666667}
| 10=2(2f+1) | | (6+4i)/(2-3i) | | 16(3x-4)=4(12X+6) | | 3x-5=7x+10 | | 11-7x=27-14x | | 320-80x=2640 | | 7x/14 | | -120-7x=140-36x | | 88x^2-2x-5=0 | | 3x^2*34-2x+5=0 | | 6x^2+15x+6=0 | | 333x^2*34-2x+5=0 | | 333x^2*34+2=0 | | 333x^2=0 | | (5x-3)(2x+4)= | | a*b*c=d | | 58-7x=11x+20 | | x^4+3=45 | | 41-3x=6x+20 | | v+x= | | 2x^2+4x+4=24 | | -12-4x=12-x | | 2x(5x+3)-(8x-2)= | | 43-3x=8x+16 | | -16x^2+1500=0 | | -16t^2+1500=0 | | 5/7b+2=27 | | 4(2x-3)=52 | | 5/7b+2=25 | | 6p=1+q | | c-45+20=455 | | -1/6(x-12)+1/2(x2)=x+3 |